2023
DOI: 10.1037/emo0001229
|View full text |Cite
|
Sign up to set email alerts
|

Fluency generating emotion words correlates with verbal measures but not emotion regulation, alexithymia, or depressive symptoms.

Abstract: How do you feel? To answer this question, one must first think of potential emotion words before choosing the best fit. However, we have little insight into how the ability to rapidly bring to mind emotion wordsemotion fluency-relates to emotion functioning or general verbal abilities. In this study, we measured emotion fluency by counting how many emotion words participants could generate in 60 s. Participants (N = 151 in 2011-2012) also completed a behavioral measure of verbal fluency (i.e., how many words s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The present usage measure was based on selfreport, and so it may diverge from active emotion vocabularies assessed in natural language. Consistent with this idea, when emotion word uency was measured in a decontextualized manner (i.e., adapting a classic semantic uency paradigm), individual differences did not predict emotion regulation or depressive symptoms (Hegefeld et al, 2023). Together, these ndings suggest that usage measures likely have complex and contextually bounded relationships with outcomes in the emotion regulation and perhaps other mental health domains.…”
Section: Discussionmentioning
confidence: 75%
“…The present usage measure was based on selfreport, and so it may diverge from active emotion vocabularies assessed in natural language. Consistent with this idea, when emotion word uency was measured in a decontextualized manner (i.e., adapting a classic semantic uency paradigm), individual differences did not predict emotion regulation or depressive symptoms (Hegefeld et al, 2023). Together, these ndings suggest that usage measures likely have complex and contextually bounded relationships with outcomes in the emotion regulation and perhaps other mental health domains.…”
Section: Discussionmentioning
confidence: 75%
“…These discrepancies suggest that the relationship between emotion word repertoires and pertinent outcomes varies based on task or context of language use. Indeed, recent work has shown that measures of emotional functioning and well-being are unrelated to fluency for emotion words, when this is assessed in a task (Hegefeld et al, 2023). Future work is necessary to probe how and when using (more) words for emotion is beneficial, and how and when it is not.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed emotional verbal fluency using a previously validated task 89 where children were asked to list all the emotions/feelings words they knew in a 30 s period during online Zoom visits (“Can you tell me all the emotion or feeling words you know? So different words for how you are feeling in your heart?…”
Section: Methodsmentioning
confidence: 99%